The Influence of Social Media Advertising and Cashback Promotions on Purchasing Decisions on Lazada - Karmila Karmila; Baiq Handayani Rinuastuti (Indonesian Development Economics and Localities, 2025)
Although Lazada has implemented social media advertising and cashback promotion strategies, consumer responses to both strategies vary. This study aims to analyze and measure the influence of social media advertising and cashback promotions on consumer purchasing decisions on the Lazada platform. The research method used is quantitative with data collection through questionnaires. The results showed that the average score for social media advertising was 20.97 and cashback promotions 20.94, indicating a positive perception of respondents towards both variables. Purchasing decisions had an average score of 21.36, indicating a positive influence of both independent variables. Statistical tests showed that social media advertising and cashback promotions had a significant effect on purchasing decisions, with an R² value of 0.689, meaning that both variables explained 68.9% of the variation in purchasing decisions. The theoretical implications of this study support the theory of consumer behavior, while the practical implications suggest that Lazada should optimize advertising and design attractive cashback promotions. This study is expected to contribute to the development of more effective marketing strategies in the future.